When a single man wants to be a father: Revealing the invisible subjects in the law regulating fertility treatment - Krajewska, Atina, and Callaghan, Rachel Cahill-O$1 s (Social & Legal Studies)
This article takes the example of single men who wish to become single fathers, using surrogacy, as a case study to examine the nature of legal subjectivity and the process by which persons acquire social visibility through legal mechanisms. The article investigates the notion of the absent subjects in law and examines the ways in which single men have been rendered invisible in the area of assisted reproduction. It investigates the emergence of legal subjectivity through the acquisition of rights in the context of fertility treatment. In this respect, it analyses the recent jurisprudence of the English courts and the changes in the human rights law that helped construct single men as subjects of law. The article proposes the concept of (in)visibilization for a number of reasons. It allows us to observe and examine the slow and contingent emergence of legal subjectivity in law. It illuminates ways, in which aspects of the critique of human rights as an inadequate vehicle of social inclusion can be overcome. In both respects, the concept of (in)visibilization provides a diction, in which we can analyse legally relevant experiences, which have not yet crossed the threshold into the formal system of law. - Reproduced
Keywords: HFE Act 2008, (In)visibilization, Invisible subjects, Legal inclusion, Legal subjectivity, Single persons